Self-medication among patients with COPD: a cross-sectional analysis in the Brazilian Public Health System - Charleston Ribeiro Pinto; Antônio Carlos Moreira Lemos; Lindemberg Assunção Costa; Aramis Tupiná de Alcântara; Laira Lorena Lima Yamamura; Eduardo Martins Neto (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2022)
The self-medication, when it occurs in an inadequate manner, may lead to a adverse reaction, interactions with prescribed medications, bacterial resistance and waste of health resources. This study seeks to identify the prevalence and the factors associated with self-medication in patients with COPD treated in the Brazilian public health care network. To answer this question, we prospectively made detailed questionnaires about drugs consumption with 383 patients whom came from the Health Care Networks and admitted into a Pharmaceutical Care Service of a Public Program Management COPD, in Salvador, Brazil. The prevalence of self-medication was 26.9%. The self-medication practice were associated with women with low education and a high number of comorbidities. This finding raises the discussion on the importance of a thorough evaluation of the usage pattern of drugs consumed by way of self-medication in patients with COPD, as a strategy to promote the rational use of medicines in the clinical practice.